Obesity and cervical intraepithelial neoplasia: regulation of mitochondrial energy metabolism via the Kisspeptin/GPR54 signaling pathway - Jiajia Pan; Yuanyuan Chen; Yan Ye; Peipei Li; Feifei Ni; Haizhen He (Cancer & Metabolism)
Abstract Background Obesity exacerbates the severity of cervical intraepithelial neoplasia (CIN), potentially through metabolic alterations. This study investigates how the Kisspeptin/GPR54 signaling pathway mediates mitochondrial energy metabolism in obesity-related CIN. Methods A clinical analysis of 980 samples was conducted to assess the correlation between Body Mass Index (BMI) and CIN grade. Transcriptomic analysis identified KISS1R as a key gene. Functional assays in cervical cancer (CC) cell lines, including CCK-8, wound healing, and Transwell assays, were used to evaluate the effects of KISS1 modulation. Mitochondrial function was assessed via oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) assays. A high-fat diet-induced CIN mouse model was used to investigate the in vivo effects. Results BMI positively correlated with CIN grade, with elevated KISS1R expression in higher CIN grades. Overexpression of KISS1 enhanced CC cell proliferation and migration by reprogramming mitochondrial energy metabolism. In high-fat environments, KISS1 silencing and mitochondrial activator PQQ modulated CC cell behavior. Activation of Kisspeptin/GPR54 in obese CIN mice exacerbated cervical lesions. Conclusion The Kisspeptin/GPR54 signaling pathway enhances mitochondrial energy metabolism, promoting obesity-related CIN grade. These findings provide a potential molecular mechanism linking obesity to CC and suggest new therapeutic targets.